Achieving quality, cost-efficiency, and consistency in blending products using enumerative with heuristic methods - Ciubal, Melchor Vergel L. 1971-
This paper shows that some medium to large-scale blending problems can be modeled as pure-integer multi-objective mathematical programs. Blending problems have usually been solved to optimality with cost-efficiency as the main driving factor. However, these optimal solutions are not always practical since certain properties like better quality, and consistency with previous blends must be present in blends if they are to be useful. In addition, there may be a minimum number of batches to be met before proceeding with actual blending. Hence, there is a need for alternative solutions. This paper claims that enumerative with heuristic methods provide more achievable a realistic alternative solutions than mathematical programs that simply obtain single optimal solutions. A decision support system which implements such a method to solve some real-world blending problems is provided. Comparisons of this proposed method with a manual method and with a relevant operations research technique are also supplied to give proof to the claim.